Risk Factors Influences Incidence of Hypertension in Lautem Municipality, Timor Leste in 2025 - Nintorio Vieira Fernandes; Mahalul Azam; RR Sri Ratna Rahayu (Universitas Negeri Semarang, 2026)
Hypertension is a leading global health problem and a major cause of cardiovascular and renal complications. In low- and middle-income countries, including Timor-Leste, its prevalence continues to rise despite ongoing prevention programs. This study examines the factors influencing hypertension in Lautem Madya City, Timor-Leste, focusing on behavioral, cultural, and socio-demographic determinants. This study uses a qualitative approach with a cross-sectional was applied using data from the Lautem Health Office. Associations between lifestyle behaviors, cultural practices, and structural barriers with hypertension prevalence were analyzed. Using a cross-sectional analytic design and Structural Equation Modeling–Partial Least Squares (SEM-PLS), 340 adult respondents (170 with hypertension and 170 without) were surveyed between January and April 2025. Data were analyzed revealed that age, gender, family history, education, diet (high salt and meat intake), smoking, alcohol consumption, limited healthcare access, and poor family support were significantly associated with hypertension (p < 0.05). Cultural practices emerged as a central factor, directly increasing hypertension risk and mediating the effects of lifestyle behaviors such as diet, smoking, and alcohol use. These findings indicate that hypertension prevention in Lautem Municipality requires culturally tailored and family-centered interventions supported by improved primary healthcare systems. This study contributes empirical evidence on the interaction of lifestyle, social, and cultural determinants of hypertension in a low- and middle-income country context.